PROSPECT OF ASIAN AMERICAN BOOK TO MOVIE ADAPTATIONS IN THE HOLLYWOOD ENTERTAINMENT INDUSTRY - Ani Windarti; Resneri Daulay; Ulaya Ahdiani; Zanuwar Hakim Atmantika (JOLALI: Journal of Language and Literature, 2023)
This paper explores the prospects of Asian American book-to-movie adaptations in the Hollywood industry. There have been a large number of book-to-movie adaptations in the history of the American film industry, such as Great Expectation (1946), The Silence of the Lamb (1991), and The Great Gatsby (2013) to mention just a few. Some have also been reported to gain fame and economic success in the global film market. The mentioned book-to-movie adaptations were based on Western authors. Meanwhile, history has witnessed the emergence of Asian American writers such as: Bharati Mukherjee, Amy Tan, Khaled Hosseini, Anchee Min, among others who have played an essential role in the field of American literature. This paper uses a qualitative method by analyzing data from selected Book-to movie adaptations. It is evident that some of them received prestigious awards. Tan’s book-to-movie adaptation The Joy Luck Club (1993), Hosseini’s book-to-movie adaptation The Kite Runner (2007) and Kevin Kwan’s Crazy Rich Asians (2018) have entered Hollywood to participate in the extremely competitive film market. The study results show that Asian American writers have emerged recently. Second, Asian American book-to-movie adaptations offer unique narratives to American audiences, although only a handful of Asian American book-to-movie adaptations have been produced. In conclusion, despite the promising growth of Asian American literature, readers can realize that Asian American book-to-movie adaptations have to struggle to be able to tap into the Hollywood industry.